Art as Power, Convenience, Aggressor and Mediator: The Artistic Force in the Work of Huda Lutfi and Amal Kenawy. Issue 4 (4th July 2017) - Sharp, Sarah
Abstract: The inclusion or exclusion of artists in Egypt's cultural matrix has always been political, and it demonstrates that the bridging of art and politics constructs modes of analysis that facilitate national transformation, cultural insight, and theory building. The artworks of artists Amal Kenawy and Huda Lutfi redefine outdated, superfluous and ignored cultural expressions and meditate on what the future may deliver. Kenawy and Lutfi exhibit creative subversions that attract attention and engage debate on issues of security versus fear, rebellion versus obedience, and stagnation versus dynamism. This study examines how Kenawy and Lutfi have committed to, managed, and controled their art production, exhibition, and images between the mid-1990s until the removal of Hosni Mubarak from the presidency in 2011.